Project Management Based Strategy Implementation - Matthews, Rupert Lawrence (2008)
The approach taken by project based companies to strategy implementation demonstrates that implementing a strategy does not need to be complicated or indeed require an excessive amount of additional resources. By investigating two companiesÃÂ¢ÃÂÃÂ approach to strategy implementation through audits, in regards to a client, the research demonstrates how different ability and focus can allow more effective strategy implementation through project based work. The research will then outline a number of situations that may be created by different amounts of focus & ability and how these situations may lend themselves to the implementation of particular strategic decisions. The research will then review how the selection and creation of a particular project network should reflect a particular strategy to improve performance and reducing total project cost.